NGO-PO campaign manual on the ADB for beginners - Ocampo, Melinda Mae Buan.; Villamor, Elizabeth Pua. (Quezon City NGO Working Group on the Asian Development Bank, 1996)
This manual serves as a tool to aid those who are just starting to understand the institution know as the Asian Development Bank. This manual contains a collection of articles written by various writers in authority in their respective fields. It includes issues on the campaign on the Asian Development Bank. Non-governmental organizations, people's organizations, community-based organizations, students, academe, international organizations, and development institutions are the target readers of this book but it may also be a resource material for the general public.
Ring bound.
Keywords: Asian Development Bank -- Handbooks, manuals, etc